PENGARUH TINGKAT PENDIDIKAN, TENAGA KERJA DAN PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI PADA 6 PROVINSI DI PULAU JAWA TAHUN 2011-2015 - Nisaa Habiballoh; M Kuswantoro; Umayatu Suiroh Suharto (Jurnal Ekonomi-Qu, 2017)
Economic growth is a key objective and an important indicator of economic development success. The purpose of this research is to analyze the influence of educational level, labor and government expenditure of education sector to economic growth in 6 provinces in Java Island in 2011-2015. The effects of development on these three sectors cannot have a direct impact but require several periods to be able to feel the impact. This research is a quantitative research, the data is processed using panel data analysis consist of cross section data as much as 6 Provinces and time series data during 2011-2015. The best regression model in this research data is REM (Random Effect Model) regression model. The results of this study indicate that the variable level of APK (SMP), education the nature of negative and insignificant relationship to economic growth in 6 Provinces in Java in 2011-2015. Labor variable is the nature of negative and signicant relation to economic growth in 6 Provinces in Java Island in 2011-2015. Govermenth education expenditure variable is the nature of positive and insignificant relation to economic growth in 6 Provinces in Java Island in 2011-2015.